Integrating information and communication technology (ICT) in education: the potential challenges and benefits (Conference on English Language Teaching, 2023)
The trend to use ICT in teaching and learning has become a standard in many educationalinstitutions. Educators consider ICT a requirement and believe that education needs tocatch up with technology development. This paper summarizes key messages of integratingInformation and Communication Technology (ICT) in education. This paper discusses thepotential challenges educational institutions face, particularly teachers when they intend touse technology in the teaching and learning process. The benefits of technology ineducation are also elaborated. ICT inclusion in education provides advantages not only tothe teachers and students but also to the school. This paper provides some basicinformation for policymakers, education specialists, ICT practitioners and a broaderaudience interested in the need for technology in the education system.